CASE STUDY: ELEARNING IN COMMUNITY OF PRACTICE FOR MANAGING BY PROJECT - Katernyak, Ihor; Niema, Oleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
New Internet technologies have expanded the possibilities of interaction, overcoming geographical restrictions. The training within communities of practices that have their own identity, determined by both the specific competencies of its participants and the common domain (field of activity, mission, values, topic), paves the way gradually in different sectors and at different levels. The research aims at generalizing the experience in organization and implementation of e-learning on Management of Projects in Community of Practice: Sustainable Development for further use and formation of virtual environments for professional training, exchange of experience, and distribution of innovations.This article summarizes the typical components of a community of practice as the basis of professional educational systems creation and knowledge management method. The paper considers the essence and prerequisites of successful e-learning. It reveals peculiarities of the virtual learning environment of the "Local Development Project Management" electronic course, which combines all the learning activities and course goals, creates the effect of social presence and co-creation. The main points of the course design should draw attention to its topics, adjust each of its elements to the needs of participants in cognition and learning, motivation for actions, cooperation, and interaction. Methods used include analysis and synthesis, induction and deduction, logical generalization, and comparison.